Yeast metabolism adaptation for efficient terpenoids synthesis via isopentenol utilization - Guangjian Li; Hui Liang; Ruichen Gao; Ling Qin; Pei Xu; Mingtao Huang; Min-Hua Zong; Yufei Cao; Wen-Yong Lou (Nature Communications)
Abstract Microbial biosynthesis has become the leading commercial approach for large-scale production of terpenoids, a valuable class of natural products. Enhancing terpenoid production, however, requires complex modifications on the host organism. Recently, a two-step isopentenol utilization (IU) pathway relying solely on ATP as the cofactor has been proposed as an alternative to the mevalonate (MVA) pathway, streamlining the synthesis of the common terpenoid precursors. Herein, we find that isopentenol inhibits energy metabolism, leading to reduced efficiency of the IU pathway in Saccharomyces cerevisiae. To overcome this, we engineer an IU pathway-dependent (IUPD) strain, designed for growth-coupled production. The IUPD strain is compelled to enhance the ATP supply, essential for the IU pathway, and incorporates a high-throughput screening method for enzyme evolution. The refined IU pathway surpasses the MVA pathway in synthesizing complex terpenoids. Our work offers valuable insights into developing growth-coupled strains adapted to efficient natural product synthesis.